Evaluating stakeholder's perspective on referred out genetic testing in Canada: a discrete choice experiment. Issue 1 (29th April 2015) - Blumenschein, P.; Lilley, M.; Bakal, J.A.; Christian, S.
Abstract : The expanding number and increasing utility of clinical genetic tests is creating a growing burden on the Canadian healthcare system. Administrators are faced with the challenge of determining which genetic tests should be publicly funded. A discrete choice experiment (DCE) was utilized to assess the importance stakeholders place on five attributes of a genetic test. One hundred ninety individuals completed the DCE questions. Analysis of the data revealed that medical benefit of a test had the greatest impact on a respondent's decision to select a test for funding. The detection rate of the test ranked second in importance followed by severity of the condition, aim of the test, and cost. With limited resources available for referred out molecular genetic testing within a public healthcare setting such as Canada's, funding guidelines are critical. Our findings provide further evidence for the value of a decision‐making framework and the relative importance of specific test attributes within such a framework. Abstract : Section Editor: Aad Tibben, email: a.tibben@lumc.nl